Relationship between digital exclusion and cognitive impairment in Chinese adults - Liu, Xiaoli; Wang, Xiaoxiao; Zhang, Hua; Pei, Minyue; Li, Nan (Frontiers in Aging Neuroscience, 2023)
Objective We aimed to evaluate the relationship between digital exclusion, such as neither mobile payments nor WeChat use, and cognitive impairment in Chinese individuals aged 45 and older. Methods A population-based cross-sectional study utilizing data from the fourth national survey of the China Health and Retirement Longitudinal Study (CHARLS). In the fourth wave of CHARLS, 10,325 participants aged 45 and older with complete information were included in this analysis. Self-reported mobile payments and WeChat usage constituted our exposure. Cognitive impairment was the primary outcome. Univariate and multivariate logistic regression were used to assess the relationships between cognitive impairment risk and digital exclusion. Results Data were analyzed from 10,325 participants [mean (SD) age, 60.3 (9.1) years; 44.8% women], including 1,232 individuals with cognitive impairment and 9,093 cognitively normal individuals. The overall proportion of users who did not use either mobile payment or WeChat and those who only used WeChat were 81.3 and 6.7%, for cognitively impaired individuals 95.0 and 3.1%, and for cognitively normal individuals 79.5 and 7.2% [neither WeChat nor mobile payments vs. control unadjusted odds ratio (OR), 8.16; P < 0.001; only WeChat use vs. control unadjusted OR, 2.91; P < 0.001]. Participants who did not use either WeChat or mobile payments had an elevated risk for cognitive impairment after adjusting for a number of covariates (neither WeChat nor mobile payments vs. control adjusted OR, 3.48; P < 0.001; only WeChat use vs. control adjusted OR, 1.86; P = 0.021). Conclusion Our study reveals a positive correlation between digital exclusion and cognitive impairment in Chinese adults, providing insights for promoting active digital integration among older adults. Further longitudinal research is needed to further validate this hypothesis.